Obesity and the Obesity Paradox in Heart Failure - Horwich, Tamara B.; Fonarow, Gregg C.; Clark, Adrienne L. (Progress in cardiovascular diseases, 2018)
Obesity continues to be a public health problem in the general population, and also significantly increases the risk for the development of new-onset heart failure (HF). However, in patients with already-established, chronic HF, overweight and mild to moderate obesity is associated with substantially improved survival compared to normal weight patients; this has been termed the “obesity paradox”. The majority of studies measure obesity by body mass index, but studies utilizing less-frequently used measures of body fat and body composition, including waist circumference, waist-hip ratio, skinfold estimates, and bioelectrical impedance analysis also confirm the obesity paradox in HF. Other areas of investigation such as the relationship of the obesity paradox to cardiorespiratory fitness, gender, and race are also discussed. Finally, this review explores various explanations for the obesity paradox, and summarizes the current evidence for intentional weight loss treatments for HF in context.